Deutsch-türkisches Kino zwischen Filmproduktion und Filmkonsum Gespräche und Analysen zu den Spielräumen filmischen Denkens - Lehmann, Hauke (Cinepoetics, 2023)
How does the way we look at a film change when it is classified as "German-Turkish cinema"? And how do we view it when we conceive of its images as products of film watching instead? In interviews with filmmakers, supplemented with analyses and theoretical reflections, this book investigates the question of the creative spaces that emerge for filmmaking between the poles of politics and art.